Lability of nanoparticulate metal complexes in electrochemical speciation analysis - van Leeuwen, Herman P.; Town, Raewyn M. (Journal of solid state electrochemistry, 2016)
Lability concepts are elaborated for metal complexes with soft (3D) and hard (2D) aqueous nanoparticles. In the presence of a non-equilibrium sensor, e.g. a voltammetric electrode, the notion of lability for nanoparticulate metal complexes, M-NP, reflects the ability of the M-NP to maintain equilibrium with the reduced concentration of the electroactive free M 2+ in its diffusion layer. Since the metal ion binding sites are confined to the NP body, the conventional reaction layer in the form of a layer adjacent to the electrode surface is immaterial. Instead an intraparticulate reaction zone may develop at the particle/medium interface. Thus the chemodynamic features of M-NP complexes should be fundamentally different from those of molecular systems in which the reaction layer is a property of the homogeneous solution ( μ = ( D M / k a ′ ) 1/2 ). For molecular complexes, the characteristic timescale of the electrochemical technique is crucial in the lability towards the electrode surface. In contrast, for nanoparticulate complexes it is the dynamics of the exchange of the electroactive metal ion with the surrounding medium that governs the effective lability towards the electrode surface.